Muslim Baduy: Conversion and Changing Identity and Tradition - Syukur, Abdul; Komarudin, Omang; Marjani, Gustiana Isya; Kahmad, Dadang (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study examines the religious transformation of the Muslim Baduy community in Leuwidamar, Lebak-Banten, with a focus on the conversion process, post-conversion religious practices, and the impact on social and cultural identity. The research aims to analyze the driving factors behind the conversion to Islam, the adaptation of religious behaviors following conversion, and the extent to which religious conversion influences socio-cultural changes among the Muslim Baduy. Employing a descriptive-analytic approach, this study utilizes an ethnographic method, incorporating participant observation, in-depth interviews, and document analysis. The findings reveal that the conversion of the Baduy people to Islam is driven by political, theological, psychological, and sociological factors. Politically, government policies supporting the welfare of isolated communities play a significant role. Theologically, Islam’s structured religious framework contrasts with the prohibitive and rigid customs of Sunda Wiwitan. Psychologically, Islam is perceived as a more accommodating and adaptable faith. Sociologically, interactions with the Muslim majority and economic constraints further influence conversion. Post-conversion, the Muslim Baduy continue cultural practices aligned with Islamic teachings while abandoning specific Sunda Wiwitan rituals. This study contributes to the discourse on religious transformation, identity negotiation, and the dynamics of indigenous belief systems in the context of Islamic integration.